Predicting Outcomes Using the Heart Failure Survival Score in Adults with Moderate or Complex Congenital Heart Disease. (31st October 2014) - Lin, Elaine Y.; Cohen, Hillel W.; Bhatt, Ami B.; Stefanescu, Ada; Dudzinski, David; DeFaria Yeh, Doreen; Johnson, Jacob; Lui, George K.
Abstract Background Adults with congenital heart disease (CHD) face increased risk for morbidity and mortality with age, but few prognostic models exist. Objective This study aims to assess whether the Heart Failure Survival Score (HFSS), which risk stratifies patients for heart transplantation, predicts outcomes in adults with moderate or complex CHD. Methods This was a multicenter, retrospective study which identified 441 patients with moderate or complex CHD between 2005 and 2013, of whom 169 had all the HFSS parameters required to calculate the risk score. Because all study patients were deemed low risk by the HFSS, the score was dichotomized at the median (10.4). Outcomes included death, transplant or ventricular assist device (VAD), arrhythmia requiring treatment, nonelective cardiovascular (CV) hospitalizations, and the composite. Associations of mean HFSS and HFSS <10.4 with each outcome were assessed. Results The cohort had mean ± standard deviation age of 33.6 ± 12.6 years, peak VO2 21.8 ± 7.5 mL/kg/min, HFSS of 10.45 ± 0.88, and median years follow‐up of 2.7 (1.1, 5.2). There were five deaths (2.8%), no transplants or VADs, 25 arrhythmias (14.8%), 22 CV hospitalizations (13%), and 39 composites (23.1%). Lower mean HFSS was observed for patients who died (9.6 ± 0.83 vs. 10.5 ± 0.87, P = .02), arrhythmia requiring treatment (10.0 ± 0.70 vs. 10.5 ± 0.89, P = .005), CV hospitalizations (9.9 ± 0.73 vs. 10.5 ± 0.88, P = .002), and the composite (10.0 ± 0.70 vs. 10.6 ± 0.89, P < .001). The positive and negative predictive values of HFSS <10.4 for the composite were 34% and 88% respectively, with sensitivity and specificity 74% and 56%. Conclusions Although a low HFSS was significantly associated with outcomes, it did not adequately risk stratify adults with CHD, whose heterogeneous pathophysiology differs from that of the acquired heart failure population. Further studies are warranted to provide a more accurate prognosis.